Application of the pentagon fraud theory in research misconduct / Dhyah Setyorini ... [et al.] - Setyorini, Dhyah; Dewanti, Patriani Wahyu; Setiani, Eko Putri; Susilo, Arief Zuliyanto (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
Higher education institutions or universities see themselves as academics who can serve as role models for future generations, and they are frequently seen as the center of advanced ethical thinking. As a result, the idea that universities might perpetrate fraud is challenging for the general public to accept. However, fraud can occur even within the scope of educational and scientific institutions. Academic fraud can harm Indonesia's ethics, morals, and intellectual culture. One type of academic fraud is research fraud. This study looked into the connection between Pentagon Fraud and fraud research. In addition, we investigated the structure of each fraud pentagon and fraud study to determine the most significant relationship between variables. The study used online surveys to research 135 academics in Indonesia. The analysis employed Canonical Correlation as the data analysis technique. The findings indicated a noteworthy and discernible correlation between Pentagon Fraud and research misconduct. The most prominent association identified between Pentagon Fraud and research fraud was attributed to pressure. This implies that the pressure experienced by individuals during research activities stands out as the primary factor contributing to research fraud.